Annexation or conquest? The economics of empire building - Herschel I. Grossman; Juan Mendoza (Brown University, Department of Economics, 2002)
This paper develops an economic theory of empire building. This theory addresses the choice among three strategies that empire builders historically have used. We call these strategies Uncoerced Annexation, Coerced Annexation, and Attempted Conquest. The theory yields hypotheses that relate the choice among these strategies to such factors as the economic gains from imperial expansion, the relative effectiveness of imperial armies, the costs of projecting imperial military power, and liquidity constraints on Þnancing imperial armies. This theory also yields hypotheses about the scope of imperial ambitions. The paper uses examples from the history of the Roman, Mongol, Ottoman, and Nazi German empires to illustrate the applicability of the theory. – Annexation ; Conquest ; Empire Building
Keywords: D74; F02; N40; 330; Großmacht; Geschichte; Wirtschaftstheorie; Theorie